Indications for Surgical Management of Osteochondritis Dissecans of the Knee in the Pediatric Population: A Systematic Review - Salci, Lauren; Ayeni, Olufemi; Abouassaly, Marcel; Farrokhyar, Forough; D'Souza, Joanne Abigail; Bhandari, Mohit; Peterson, Devin (The Journal of Knee Surgery, 2014)
Several case series have been published exploring the surgical management of osteochondritis dissecans (OCD) of the knee in pediatric patients. This systemic review was performed to identify the surgical indications for this condition. A search of the Embase and Ovid Medline databases was performed to identify clinical studies reporting outcomes of surgical management of OCD in the knee in this patient population. A quality assessment of the included articles was conducted independently by two reviewers using a quality assessment tool developed by Yang et al. A total of 25 articles met the eligibility criteria and were reviewed; 40% of studies did not clearly describe their surgical indications. The remainder of the studies had a failure of nonoperative management with or without the concomitant use of imaging as their indication for surgery, or used lesion stability itself as the indication for surgery. This review outlines several surgical indications presented in the literature for the treatment of OCD lesions of the knee in the pediatric population. The most common indication for surgery was a failure of a trial of nonoperative treatment with or without the concomitant use of serial imaging. Although the quality of the case series was high, inconsistencies in reporting radiographic and arthroscopic classification of the OCD lesion were common.
Keywords: osteochondritis dissecans; knee; pediatric; systematic review